Neural and computational mechanisms of momentary fatigue and persistence in effort-based choice - Tanja Müller (Nature Portfolio, 2021)
The willingness to exert effort into demanding tasks often declines over time through fatigue. Here the authors provide a computational account of the moment-to-moment dynamics of fatigue and its impact on effort-based choices, and reveal the neural mechanisms that underlie such computations.